Does trade openness affect bank risk-taking behavior? Evidence from BRICS countries - Mohammed Mizanur Rahman; Munni Begum; Badar Nadeem Ashraf; Md. Abdul Kaium Masud (Economies, 2020)
In this paper, we examine the impact of trade openness on bank risk-taking behavior employing a panel dataset of 899 banks from the BRICS (i.e., Brazil, Russia, India, China, and South Africa) countries over the period 2000-2017. We find that higher trade openness lowers bank risk-taking. Our results are robust when we use alternative proxies of trade openness and bank risk-taking, estimate country-wise regressions, or use alternative estimation methods such as system Generalized Methods of Moments (GMM), fixed effects, pooled Ordinary Least Square (OLS), and Vector Error Correction Model (VECM) models. We also observe higher trade openness decreases bank risk-taking in both the short and long run. Moreover, banks in more open countries perform relatively better during the crisis period further signifying the diversification benefits of openness. Together, our findings imply the beneficial impact of trade openness for financial sector stability.
Keywords: 330; trade openness; bank risk-taking; financial crisis; financial stability; system GMM; VECM